2021
DOI: 10.26574/maedica.2021.16.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Left Atrial Volume Evaluated by 3D Echocardiography Predicts Atrial Fibrillation Recurrences After a First Radiofrequency Catheter Ablation for Paroxysmal Episodes

Abstract: Background: Atrial fibrillation (AF) is facilitated by an enlarged left atrium (LA) and increased LA mass. Left atrium volume (LAV) has a powerful prognostic value for sinus rhythm (SR) maintenance. Persistent SR may lead to atrial reverse-remodeling; therefore, preprocedural LAV may predict the outcome after AF radiofrequency catheter ablation (RFCA).Study aim: To evaluate the relationship between LA dimensions and AF recurrences (AFR) using echocardiography.Methods: We enrolled 40 patients (56 ± 10 years; 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Among the various LA imaging parameters, LAVmax has been the most extensively assessed biomarker [ 1 – 5 ]. More recently, there has been increasing interest for LAVmin, which has shown a greater prognostic value than LAVmax [ 23 25 ] and may reflect the ‘contractile’ function of the LA more precisely [ 26 , 27 ]. LAEF is another relevant parameter, since it showed the best correlation with E/Eʹ values in a population of patients with diastolic dysfunction assessed by echocardiography [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the various LA imaging parameters, LAVmax has been the most extensively assessed biomarker [ 1 – 5 ]. More recently, there has been increasing interest for LAVmin, which has shown a greater prognostic value than LAVmax [ 23 25 ] and may reflect the ‘contractile’ function of the LA more precisely [ 26 , 27 ]. LAEF is another relevant parameter, since it showed the best correlation with E/Eʹ values in a population of patients with diastolic dysfunction assessed by echocardiography [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In sum, the determination of parameters of LA remodeling for predicting patients with high risk of recurrence after CA plays a significant role in assisting clinicians in making more specific therapeutic strategy. LA size can determine the risk of recurrence of AF in patients after CA [ 87 ]. Additionally, LA strain evaluated by 2D-STE has been demonstrated as an independent predictor of AF recurrence after CA [ 88 , 89 , 90 ], however, 2D-STE is limited by its dependency on image quality and the out-of-plane motion of some speckles, which may overestimate LA function [ 68 ].…”
Section: La Structure and Function To Predict The Recurrence Of Af Af...mentioning
confidence: 99%
“…The maximum volume is the most evaluated parameter associated with AF [30,31,39], but more recent studies concentrated on LA minimum volume as a marker of prognosis [40][41][42][43]. Appleton et al [44] showed that minimum LA volume is more closely related to left ventricular filling pressures evaluated invasively, compared to maximum LA volume.…”
Section: Left Atrial Size In Afmentioning
confidence: 99%
“…The maximum volume is the most evaluated parameter associated with AF [ 30 , 31 , 39 ], but more recent studies concentrated on LA minimum volume as a marker of prognosis [ 40 , 41 , 42 , 43 ]. Appleton et al .…”
Section: Left Atrial Size In Afmentioning
confidence: 99%